Electromyography findings in L5 radiculopathy are not associated with fatty infiltration of paraspinal muscles: a retrospective observational study - Seliverstova, Ekaterina; Sinkin, Mikhail; Grin, Andrey (Frontiers in Neurology, 2024)
IntroductionIncreased fatty infiltration of the paraspinal muscles (PM) has been recognized as a sign of decreased muscle quality in patients with degenerative disc disease. However, whether fatty infiltration is a consequence of a neurogenic process due to spinal nerve root compression has not yet been determined.ObjectiveTo investigate the correlation between fatty infiltration of the paraspinal muscles (PM) and neurogenic remodeling of motor unit action potentials (MUAPs) in patients with lumbar radiculopathy.Materials and methods58 adult patients (32 women) with L5 radiculopathy caused by an L4-L5 herniated disc were examined. We compared the neurological status, EMG data of the PM at the L5 level on the affected side and the L4 level on the opposite side of the spine, and the severity of fatty infiltration of the PM assessed on axial T2-weighted magnetic resonance imaging (MRI) scans.ResultsWe did not find any correlation between the degree of fatty infiltration and neurogenic remodeling of MUAPs in the PM.ConclusionThe lack of correlation between the degree of fatty infiltration and the presence of neurogenic remodeling of MUAPs in the PM suggests that fatty infiltration and neuropathic changes in muscles may be considered as separate processes requiring further research.